65 Junior doctor engagement in rota writing during the COVID 19 crisis. (16th November 2020) - Gargan, Alice; Dunhill-Turner, Natasha; Ireland, Dervla; Mitchell, Colin
Abstract : The COVID-19 pandemic placed an unprecedented demand on the NHS. In response, high-intensity rotas were implemented with short notice. This project aimed to fairly and safely step down the COVID response rota as normal working patters resumed. Assessment: A cross-sectional survey was distributed to doctors on the medical COVID rota. It explored their views on the step-down process. The majority of respondents (68%) had concerns including discrepancy between on calls and lack of opportunity to plan leave. A document of key themes in the feedback was prepared and presented to senior clinical managers. Intervention and Improvement: The new rota produced ensured an even distribution of shifts and honoured pre-existing leave. The new rota was compliant and ran to completion for every trainee. Comparison of stepping down to the trust rota vs our new rota reduced inter-trainee shift variation. Night shift discrepancy SD reduced from 2.89 to 0.97, long day (ward cover) on-calls reduced from SD 3.57 to 1.12 and long day (take) shifts SD 0.98 to 0.56. Following implementation a second cross-sectional survey was distributed. 85% agreed or strongly agreed that there was sufficient staffing levels 'on call' and 80% agreed or strongly agreed that there was sufficient staffing levels on the wards. 95% found they were able to take their annual leave and 80% agreed or strongly agreed that there was an even distribution of on-call and night shifts. Conclusion: The success of our project relied on good engagement with colleagues to collect a representative view for leverage in discussions with seniors, and produced a result that was fairer for trainees, sustainable, and preferable for rota coordinators and senior clinical management. Active collaboration in the rota design process will improve junior doctor engagement, well-being and job satisfaction.